铰链六杆机构的动力学分析系统 - 闵剑青; 徐梓斌; 舒建武 (Jixie chuandong)
SimMechanicd, a dynamic simulation tool, is briefly introduced, and a method for dynamic analysis using simulation is presented. The gemel six-bar mechanism is taken as an example and it is known that SimMechanics has the powerful advantage of convenient and visual modeling function, powerful simulation function, automatic model analysis function and so on, it can be used to analyses various motion in mechanical system, this method can be a powerful and convenient tool in mechanical system analysis and simulation.